Towards investigation of external oil flow from a journal bearing in an epicyclic gearbox - Berthold, Martin; Morvan, Herve; Young, Colin; Jefferson-Loveday, Richard J. (American Society of Mechanical Engineers, 2018)
High loads and bearing life requirements make journal bearings the preferred choice for use in high power, planetary gearboxes in jet engines. With the planet gears rotating about their own axis and orbiting around the sun gear, centrifugal forces generated by both motions interact with each and generate complex kinematic conditions. This paper presents a literature and state-of-the-art knowledge review to identify existing work performed on cases similar to external journal bearing oil flow. In order to numerically investigate external journal bearing oil flow, an approach to decompose an actual journal bearing into simplified models is proposed. Preliminary modeling considerations are discussed. The findings and conclusions are used to create a three dimensional (3D), two-component computational fluid dynamic (CFD) sector model with rotationally periodic boundaries of the most simplistic approximation of an actual journal bearing: a non-orbiting representation, rotating about its own axis, with a circumferentially constant, i.e. concentric, lubricating gap. In order to track the phase interface between the oil and the air, the Volume of Fluid (VoF) method is used. External journal bearing oil flow is simulated with a number of different mesh densities. Two different operating temperatures, representing low and high viscosity oil, are used to assess the effect on the external flow field behaviour. In order to achieve the future objective of creating a design tool for routine use, key areas are identified in which further progress is required.